PENINGKATAN KETERLIBATAN ORANG TUA DALAM PENDIDIKAN SEKS ANAK - Eny Purwandari (Universitas Muhammadiyah Surakarta, 2018)
The fulfillment of children sexual education is still ignore,the sex education for children is watched as something negative and still dificult to be educated to children.The parents has an important role for the children sexual education because the parents is the first teacher for the children. So that is the reason, there should have an effort to give an explaination to the children about the function of their sexual organs.To get komperhensive understanding, it was done survey towards 80 parents, in one of Elementary school in Sragen.This reseach used kualitatif approach with fenimenology methode. To get the data the researcher used open questionair